Forecasting and analysing the gap between Thailand’s wood pellet supply and global demand - Koondee, Phongsathon; Niemsakul, Jirawan; Supeekit, Tuangyot; Somboonwiwat, Tuanjai; Chanpuypetch, Wirachchaya (Engineering and Applied Science Research, 2023)
With the global concern for climate change on the rise, the use of biomass wood pellets as a sustainable alternative to fossil fuels is gaining popularity in numerous countries, such as the European Union (EU), the United States, Canada, Japan, and South Korea. In response, the Thai government has initiated a project to promote the cultivation of fast-growing trees, such as Acacia, which can serve as feedstock for biomass power plants both domestically and internationally. The objective of this study is to evaluate the demand-supply gap for wood pellets in Thailand. To predict future demand for wood pellets, historical import data from January 2017 to December 2021 were examined and analysed, with a variety of time-series forecasting techniques, including the Simple Moving Average (SMA), the Holt’s Two-Parameter method, and the ARIMA method, being employed. The appropriate techniques were subsequently chosen based on the Mean Absolute Deviation (MAD), Mean Square Error (MSE), and Mean Absolute Percentage Error (MAPE). The results of the analysis can be utilised to identify market gaps and growth opportunities, and to develop a comprehensive supply chain strategy for wood pellets, ranging from upstream tree plantation to downstream demand.